تعليم اللغة العربية بالأحاديث النبوية (تطبيق المنهاج المتكامل) - Husen, Usman (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2020)
An integrated curiculum lessons has taken place in the history of Islamic education in the middle century. At that time, many scholars integrated a number of knowledges in their books to reviewed the material deeply. In the modern world now has felt the integration of language curriculum into Islamic religious knowledge is need. So this maqalah tries to put forward of teaching Arrabic that is integrated with hadith lesson. Thus, the students apply Arabic grammar in various disciplines of knowledge, as hadith, and also makes it easy for them to understand the purpose of the hadith or other Islamic knowledge. Teachers who apply Arabic grammar in the hadith texts at the same time they teach two fields of knowledge